Proteomic analysis of human glutathione transferase omega (hGSTO1) stable transfection in a 6-hydroxydopamine-induced neuronal cells - Jeerang Wongtrakul (2018)
© 2018 Slovak Academy of Sciences. All rights reserved. Parkinson's disease is the second most common neurodegenerative disorder after Alzheimer's disease. The disease is associated with dopaminergic neuron losses in the substantia nigra area of the brain and the formation of cytoplasmic inclusion bodies. Human glutathione transferase omega 1 (hGSTO1) appears to have a role in modulating stress response. The study was aimed to elucidate differentially expressed proteins caused by oxidative stress induced by 6-hydroxydopamine (6-OHDA). Human neuronal cells SH-SY5Y overexpressing hGSTO1 were used to investigate protein glutathionylation and the modulation of cellular protein expression. Therefore SH-SY5Y/hGSTO1 and SH-SY5Y/control lysate proteins were separated by 2D-gel electrophoresis compared with untreated conditions in both standard and non-reducing conditions. In standard conditions, the analysis of protein profiles demonstrated 25 differentially expressed spots and 10 spots were chosen for further protein identification by LC-MS analysis. Several proteins were later identified as vimentin, galectin-1, high mobility group protein B2, clathrin, tropomyosin, heterogenous nuclear ribonucleoprotein and peroxiredoxin-2. Search Tool for Interactions of Chemicals (STITCH) analysis suggested that oxidative stress induced by 6-OHDA involved carbohydrate metabolism in SH-SY5Y via a lactose metabolic pathway. Our results raise the possibility that hGSTO1 modulates the functions of many proteins that play a role in the degenerative cell response of a Parkinson's model.